The effects of Tai Chi and Baduanjin on breast cancer patients: systematic review and meta-analysis of randomized controlled trials - Chen, Yifang; Tang, Yong; Zhou, Zhimiao (Frontiers in Oncology, 2024)
BackgroundTai Chi and Baduanjin are nonpharmacological interventions that are widely applied among cancer patients.ObjectiveThis meta-analysis aimed to assess the effect of Tai Chi and Baduanjin on breast cancer patients by summarizing and pooling the results of previous studies.MethodsThe PubMed, Embase, Web of Science, Scopus and Cochrane Library and several databases were searched up to December 1, 2023, to identify high-quality RCTs. Relevant terms such as Tai Chi and Baduanjin were used as keywords. Stata 15.0 software and Review Manager (version 5.3; Cochrane Training) were used to screen the studies, extract the data, code the data, and perform the meta-analysis. The mean differences (MDs) and standardized mean differences (SMDs) with 95% CIs were used to calculate continuous variables. The Cochrane risk of bias assessment tool was used to evaluate the risk of bias. The PICOS framework was used to develop the following eligibility criteria: (i) population - breast cancer patients; (ii) intervention - Tai Chi and Baduanjin intervention; (iii) comparison - Tai Chi and Baduanjin group and different intervention (e.g., regular intervention, routine rehabilitation training, waiting list, sham Qigong, usual care, no intervention); (iv) outcomes - cognitive ability, shoulder joint function, anxiety, depression, fatigue, sleep quality, quality of life; and (v) study design - randomized controlled trial.ResultsFrom January 2013 to December 2023, we included a total of 16 RCTs involving 1247 patients. A total of 647 patients were in the experimental group and were treated with Tai Chi and Baduanjin, while 600 patients were in the control group and were treated with traditional methods. The results of our meta-analysis indicate that Tai Chi and Baduanjin yield outcomes that are comparable to those of traditional treatment methods. Specifically, Tai Chi and Baduanjin significantly increased cognitive function, increased shoulder joint function, improved sleep quality indicators and improved quality of life indicators. Furthermore, Tai Chi and Baduanjin significantly reduced anxiety symptoms, depression symptoms, and fatigue symptoms among breast cancer patients. Sensitivity analysis was performed, a funnel plot was constructed. No publication bias was indicated by Egger’s or Begg’s test.ConclusionOverall, Tai Chi and Baduanjin are viable and effective nonpharmacological approaches for treating breast cancer patients, as they yield better results than traditional treatment methods. However, these findings should be interpreted with caution due to the limited number of controlled trials, small sample sizes, and low quality of the evidence.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023469301.